PENOKOHAN DALAM KUMPULAN CERPEN “SEPOTONG HATI YANG BARU” KARYA TERE LIYE - Maguna Eliastuti; Lina, Lina; Runi Ari Wandani; Rizki Daniyanti; Wulandari (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
Literary works are born because of something that makes the soul of an author or creator have a certain sense of a problem or event in this world, both what he directly experiences and from the realities of everyday life in society. These problems and events can also affect the characterization of his work. Therefore, the purpose of this research is to identify and analyze the use of characterizations in the short story collection "Sepotong Hati yang Baru" by Tere Liye. The method used in this study is a qualitative descriptive method with content analysis techniques. After the writer analyzes the characterizations in the collection of Sepotong Hati yang Baru short stories, finally the writer can draw the conclusion that the type of characterization that dominates the short story collection of Sepotong Hati Baru is the protagonist.